Effects of salinity on the growth, physiological and biochemical components of microalga Euchlorocystis marina - Pan, Yao; Amenorfenyo, David Kwame; Dong, Mingbiao; Zhang, Ning; Huang, Xianghu; Li, Changling; Li, Feng (Frontiers in Marine Science, 2024)
Euchlorocystis marina, a new marine species of the genus Euchlorocystis discovered in 2022, has the potential to improve the water quality in mariculture ponds. However, the effects of salinity on the growth, physiology, and biochemical composition of these algae are not well understood. In this study, changes in physiological and biochemical indices such as cell density, photosynthetic pigment, polysaccharide, and lipid content of E. marina under different salinity treatments were analyzed. The results showed that the highest cell density was observed at a salinity of 15‰. The lowest photosynthetic pigment content was observed at a salinity of 60‰, and the highest polysaccharide and lipid content was observed at a salinity of 60‰. These results indicated that lower salinity was more conducive to E. marina reproduction and growth. E. marina can accumulate polysaccharides and lipids in high salinity environments. This study provides new information for understanding the salinity adaptation strategies of E. marina and has practical significance for its development and utilization.